Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar Pada Muatan IPA Materi Siklus Air Menggunakan Model MERDEKA Siswa Kelas 5A SDN Kelayan Selatan 10 Banjarmasin - Rima Yanti; Mahmuddin (CV. ITTC INDONESIA, 2024)
The problem in this study are critical thinking skills and low student learning outcomes. The effort to overcome these problems is by using the MERDEKA model. The purpose of this study was to describe students’ activities, teachers’ activities, and analyze the improvement of critical thinking skills and students’ learning outcomes. This research was conducted with the type of Classroom Action Research (CAR) for 4 meetings. The subjects of this research is class 5A studentd as many as 27 students consisting of 14 male students and 13 female students. Qualitative data was obtained by observing teacher activities. student activities, critical thinking skills. While quantitative data is obtained by conducting written tests both individually and in groups. The result of this study showed that the teacher’s activity at meeting 4 obtained a score of 32 with the category “Very Good”. Student activity at meeting 4 obtained a classical persentage of 100% with the category “All Students are Very Active”. Critical thinking skill at meeting 4 obtained a percentage of 93% with the category “Almost All Students are Very Skilled”. Cognitive aspect learning outcomes obtained a classical persentage of 100%. Affective aspect learning outcomes obtained a classical persentage of 100%. Learning outcomes of psychomotor aspects obtained a classical percentage of 93%.